Improved packing performance and structure-stability of casein edible films by dielectric barrier discharges (DBD) cold plasma. (June 2020) - Wu, Xiaomeng; Liu, Qi; Luo, Yanghe; Murad, M. Safian; Zhu, Linxian; Mu, Guangqing
Graphical abstract: Highlights: Mechanical performance and barrier property of casein film were improved. Crystalloid migration affects films' structure stability and packing characters. Cold plasma successfully improved stability and packing characters of casein films. Abstract: This study utilized dielectric barrier discharges (DBD) cold plasma technique to improve the packing characters of casein edible films. It was found that with DBD cold plasma discharge treatment, the crystalloid migration and casein aggregation occurred in casein based films could be seen clearly by scanning electron microscopy (SEM). A little change of crystal structure and stable state of molecule structure was obtained in casein from X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) results, respectively. Importantly, packing characters including tensile strength, elongation, thermo stabilization and barrier property were improved remarkably with DBD cold plasma treatment. In addition, slight modifications of color and transparency were revealed with cold plasma discharge reinforced. These phenomena could be owe to crystalloid migrated with plasma discharge treatment leading to the arrangement of order among protein and crystalloid varied and transferred in the casein based films. Therefore, DBD cold plasma successfully facilitated the packing characters of casein based films development. And this study would be a basis for the research on improving property of protein films via a behavior of cold plasma treatment.